Non-linear effects of self-compassion and negative psychological states on nurses’ work engagement - Hongjuan Chang; Rui Zeng; Qianqian Gao; Yu Zhang (Scientific Reports)
Abstract The state has formulated relevant policies to improve nurses’ work engagement, but the research on work engagement among clinical nurses and related factors is limited and mostly linear. This study used an online questionnaire to investigate responses from 3352 nurses from East, West, South, North, and Central China. Threshold and saturation effects analysis were used to explore the possible non-linear relationship between self-compassion, negative psychological states, and work engagement. When the self-compassion score was ≤ 92, the work engagement level increased by 0.223 points for every 1-point increase of the self-compassion score, and the difference was statistically significant (β = 0.223, P < 0.001). When the negative psychological states scores were ≤ 41 and ≥ 72, for every 1-point decrease in the negative states score, the level of work engagement decreased by 0.430 and 3.660 points, respectively, and the difference between them was statistically significant (β = − 0.430, − 3.660, P < 0.001). In particular, the threshold effect was the most significant after 72 points. This study reveals the non-linear relationships between self-compassion, negative psychological states, and work engagement among clinical nurses, and it suggests nursing managers should target interventions based on cut-off points to maximize the contribution of self-compassion and negative psychological states to work engagement.